The Influence Of A Botanical Garden Experience on Human Health - Owen, Patricia J. (Kansas State University, 1994)
Physiological and psychological measurements of 127 visitors to a botanical garden were collected to determine the influence of a garden environment. Physiological measurements were recorded before and after participants visited the gardens. A pre-visit survey identified emotional expectations of the garden visit. Post-visit surveys ascertained participants' emotional impressions. Length of visit, ambient air temperature, and participants' health related data were recorded. Participants' average systolic blood pressure measurements decreased significantly on three of the four days studied. Participants' mood state before and after visiting the gardens were significantly influenced. Self-reports of participants as well as physiological measurements indicate both physiological and psychological benefits of visiting a botanical garden.